2018
DOI: 10.1016/j.anorl.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 3D printing to mandibular reconstruction after cancer

Abstract: Three-dimensional (3D) printing is booming in the medical field. This technology increases the possibilities of personalized treatment for patients, while lowering manufacturing costs. To facilitate mandibular reconstruction with fibula free flap, some companies propose cutting guides obtained by CT-guided moulding. However, these guides are prohibitively expensive (€2,000 to €6,000). Based on a partnership with the CNRS, engineering students and a biomedical company, the authors have developed cutting guides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 7 publications
0
38
0
2
Order By: Relevance
“…A wave of virtual surgical planning (VSP) has recently emerged as an improvement on the traditional freehand approach. [3][4][5][6][7][8][9][10][11][12] Although the specifics of VSP vary, they all follow the general workflow of segmenting radiological data to create a 3D model, planning on the model, and using surgical guides to carry out the reconstruction plan. Generally, VSP can be divided into three modes: external planning through a commercial planning service in which the surgeon has a virtual meeting with the third party, 7,9,11 in-house planning using commercial dedicated planning software, 4,5,10 and, less commonly, in-house planning using a custom software workflow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wave of virtual surgical planning (VSP) has recently emerged as an improvement on the traditional freehand approach. [3][4][5][6][7][8][9][10][11][12] Although the specifics of VSP vary, they all follow the general workflow of segmenting radiological data to create a 3D model, planning on the model, and using surgical guides to carry out the reconstruction plan. Generally, VSP can be divided into three modes: external planning through a commercial planning service in which the surgeon has a virtual meeting with the third party, 7,9,11 in-house planning using commercial dedicated planning software, 4,5,10 and, less commonly, in-house planning using a custom software workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, VSP can be divided into three modes: external planning through a commercial planning service in which the surgeon has a virtual meeting with the third party, 7,9,11 in-house planning using commercial dedicated planning software, 4,5,10 and, less commonly, in-house planning using a custom software workflow. 3,8,12 VSP has been shown to reduce operating and ischemia time, [4][5][6]13 and in some cases shown to improve the accuracy of reconstructions compared to the standard freehand approach. 4,5,14 The drawback of commercial options is that they are expensive, on This work has not been published or presented anywhere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the development of three-dimensional printing (3DP) technology for tissue engineering has contributed to increased speed and precision from planning to operation in maxillofacial reconstruction 6 . 3DP technology has been researched in manufacturing scaffolds with growth factor in conjunction with a surgical guide and template.…”
mentioning
confidence: 99%
“…3D printing prototype models can significantly assist with preoperative evaluation and intraoperative procedures, for example for the use of surgical guides in mandibular reconstruction with osteocutaneous flaps (Bosc et al, 2017;Dupret-Bories et al, 2018). These studies showed the advantages of using 3D printed preoperative models and surgical guides including a reduction in operating time, flap ischemia, morbidity and associated complications such as infections.…”
Section: D Printing In Bone Tissue Engineering Applicationsmentioning
confidence: 99%